C60 concrete by using desert sands for substituting sands used for steel pipe concrete - HAN LINHAI; HOU CHAO; REN QINGXIN; TAO ZHONG (2016)
The invention relates to a C60 concrete by using desert sands for substituting sands used for steel pipe concrete, which belongs to the technical filed of building material concrete preparation in civil engineering. The C60 concrete is produced by mixing cement, broken stone, desert sands, water, fly ash and a water reducer, wherein, the ratio of cement to broken stone to desert sands to water to fly ash to the water reducer is (361-399): (808-893): (765-845): (167-185): (162-179): (10-12). In a formula of the concrete, the desert sands are used for completely substituting the river sands in the traditional concrete, the resource of the river sands is saved, building energy consumption is reduced, raw materials are easily available, environmental protection is realized, effective utilization of natural resource is achieved, a solution scheme is provided, at the same time, the concrete has the advantages of good fluidity, large slump degree, strong self-compacting ability, high intensity at an early stage, and